Prevalence and factors associated with urinary incontinence in elderly women - Karla Veruska Marques Cavalcante; Maria Isabel Gomes da Cruz Silva; Adan Smith Ferreira Bernardo; Damião Ernane Souza; Thereza Christina da Gama Cunha Lima; Adriana Gomes Magalhães (Universidade de Fortaleza, 2014)
Objective: To verify the prevalence of urinary incontinence (UI) complaints and associated factors among elderly women in the municipality of Petrolina / PE. Methods: Exploratory cross-sectional study conducted in 2009 with 172 elderly women who were assessed regarding sociodemographic, socioeconomic and lifestyle characteristics. UI was assessed using The International Consultation on Incontinence Questionnaire - Short Form (ICIQSF) in addition to questions on obstetrics and comorbidities. Data were computed with a 95% confidence interval using STATA 9.0. Results: The urinary incontinence was present in 81 (47.1%) elderly women. The age group older than 75 years was associated with UI (PR1.57 CI 95% 1.57 - 11.09). Regarding the association with occupation, it was verified that both the retired elders (PR 4.64 CI 95% 0.98 - 21.98) and housewives (PR 6.25 CI 95% 1.14 - 34.12) were more likely to report UI, but only the association with the housewife condition was significant. With regard to diabetes, elderly women who had the disease (PR 1.57 CI 95% 1.16 - 2.13) were more likely to report urinary incontinence when compared to elderly women without diabetes. Conclusion: There was a high prevalence of urinary incontinence among elderly women, which accounted for almost half of the women assessed and was associated with older age, housewives and diabetes. doi:10.5020/18061230.2014.p216